2004
DOI: 10.1128/jcm.42.1.408-411.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA Polymerases and Their Buffer Systems on Quantitative Real-Time PCR

Abstract: An investigation of the influence of five DNA polymerase-buffer systems on real-time PCR showed that the choice of both DNA polymerase and the buffer system affected the amplification efficiency as well as the detection window. The analytical repeatability of the data for different systems changed clearly, leading us to conclude that basing quantitative measurements on single-data-set standard curves can lead to significant errors.Sequence-specific nucleic acid quantification in areas such as diagnostic PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…Buffer components may also be important in the sense that compounds present in the buffer system of one DNA polymerase may be beneficial for the activity of the other polymerase in the blend. The presence or absence of PCR facilitators is a well-known factor determining the amplification efficiency of DNA polymerases in general [35], and several different compounds have been used to counteract PCR inhibition [25]. Examples of PCR facilitators that have been shown to increase inhibitor tolerance include proteins such as BSA [14,26] and nonionic detergents such as Tween 20 and Triton X-100 [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Buffer components may also be important in the sense that compounds present in the buffer system of one DNA polymerase may be beneficial for the activity of the other polymerase in the blend. The presence or absence of PCR facilitators is a well-known factor determining the amplification efficiency of DNA polymerases in general [35], and several different compounds have been used to counteract PCR inhibition [25]. Examples of PCR facilitators that have been shown to increase inhibitor tolerance include proteins such as BSA [14,26] and nonionic detergents such as Tween 20 and Triton X-100 [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that qPCR can be improved by the use of alternative DNA polymerases, such as Tth (28). By using this DNA polymerase and its buffer in flotationqPCR, quantification was possible over a range of at least 5 log units (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR conditions. A primer set targeting a 0.3-kb part of the 16S rRNA gene from Y. enterocolitica (16) was used to develop a real-time PCR assay using the LightCycler instrument (Roche Diagnostics, Mannheim, Germany) (28). The PCR mixture consisted of 0.75 U of Tth DNA polymerase (Roche Diagnostics); 1ϫ Tth DNA polymerase buffer (Roche Diagnostics); 4 mM MgCl 2 ; 0.4 M each primer; 0.2 mM (each) dATP, dCTP, dGTP, and dTTP; 10,000-fold-diluted SYBR Green I (Roche Diagnostics); and 4 l of sample.…”
Section: Methodsmentioning
confidence: 99%
“…Their study [16] used one signature set and examined the ability of certain PCR enzymes to amplify in the presence of common PCR-inhibiting components found in complex biological samples. Subsequently, Wolffs et al [17] investigated four DNA polymerases (Taq, DyNazyme, Tth and rTth) and two different buffer systems in real-time PCR and showed that the choice of both the type DNA polymerase and the buffer system affected amplification efficiency. In our study, we compared 10 commercial reagents by the use of real-time PCR assays for four different select agents in an effort to provide a thorough evaluation of the most popular kits that are currently on the market.…”
Section: Discussionmentioning
confidence: 99%